Visual six sigma : making data analysis lean / Ian Cox, Marie A. Gaudard, Mia L. Stephens. - Cox, Ian,
"Streamline data analysis with an intuitive, visual Six Sigma strategy Visual Six Sigma provides the statistical techniques that help you get more information from your data. A unique emphasis on the visual allows you to take a more active role in data-driven decision making, so you can leverage your contextual knowledge to pose relevant questions and make more sound decisions. You'll learn dynamic visualization and exploratory data analysis techniques that help you identify occurrences and sources of variation, and the strategies and processes that make Six Sigma work for your organization. This updated third edition includes new information on data quality, presentation, and analysis, with new, streamlined case studies featuring the latest functionalities in JMP 11 and JMP 11 Pro, complete with illustrative screenshots. The companion website includes a test bank, end-of-chapter questions, and free 30-day access to a fully functional demo version of JMP software from the SAS Institute, so you can immediately begin putting your newfound knowledge to work. The Six Sigma strategy helps you identify and remove causes of defects and errors in manufacturing and business processes; the more pragmatic Visual approach opens the strategy beyond the realms of statisticians to provide value to all business leaders amid the growing need for more accessible quality management tools. See where, why, and how your data varies Find clues to underlying behavior in your data Identify key models and drivers Build your own Six-Sigma experience Whether your work involves a Six Sigma improvement project, a design project, a data-mining inquiry, or a scientific study, this practical breakthrough guide equips you with the skills and understanding to get more from your data. With intuitive, easy-to-use tools and clear explanations, Visual Six Sigma is a roadmap to putting this strategy to work for your company"--